Freehand Versus Guided Surgery: Factors Influencing Accuracy of Dental Implant Placement. Issue 4 (August 2017) - Choi, William; Nguyen, Bao-Chau; Doan, Andrew; Girod, Sabine; Gaudilliere, Brice; Gaudilliere, Dyani
Abstract : Introduction: Patient anatomy, practitioner experience, and surgical approach are all factors that influence implant accuracy. However, the relative importance of each factor is poorly understood. The present study aimed to identify which factors most critically determine implant accuracy to aid the practitioner in case selection for guided versus freehand surgery. Methods: One practitioner's ideal implant angulation and position was compared with his achieved position radiographically for 450 implants placed using a conventional freehand method. The relative contribution of 11 demographic, anatomical, and surgical factors to the accuracy of implant placement was systematically quantified. Discussion: The most important predictors of angulation and position accuracy were the number of adjacent implants placed and the tooth-borne status of the site. Immediate placement also significantly increased position accuracy, whereas cases with narrow sites were significantly more accurate in angulation. Accuracy also improved with the practitioner's experience. Conclusion: These results suggest tooth-borne, single-implant cases performed later in the practitioner's experience are most appropriate for freehand placement, whereas guided surgery should be considered to improve accuracy for multiple-implant cases in edentulous or partially edentulous sites.